The Impact of COVID-19 Pandemic on Emerging Country Stock Markets: Evidence of the Value Effect. Issue 1 (2nd January 2022) - Yang, Yang; Li, Lingyi; Jiang, Jialing
ABSTRACT: We examine the impact of the COVID-19 pandemic on seven emerging stock markets by focusing on the value effect. Our results show that there are significant differences in the value premia before and during the pandemic. Furthermore, the traditional value proxies are no longer good predictors of future stock returns. To further capture the impact the pandemic's progress on stock returns, we estimate Fama-MacBeth regressions by introducing proxies of the pandemic. We uncover heterogeneous responses of emerging markets to the pandemic. These findings provide a wealth of insights on the presence and driving force relevant to the value effect.